On the Detection of CE-OFDM Signals - Guerreiro, João (2016)
— In this letter, we study the optimum performance of constant envelope orthogonal frequency division multiplexing (CE-OFDM) signals in both ideal additive white Gaussian noise channels and frequency-selective channels, and we compare it to the performance of conventional CE-OFDM receivers based on a phase detector. It is shown that the phase detector can achieve optimum performance, but only in scenarios where the power efficiency is very low. For this reason, the use of CE-OFDM schemes in power-constrained scenarios may demand other type of receivers, such as optimum-based receivers.